Idarucizumab for Emergency Reversal of Anticoagulant Effects of Dabigatran: Interim Results of a Japanese Post-Marketing Surveillance Study - Masahiro Yasaka; Hiroyuki Yokota; Michiyasu Suzuki; Hidesaku Asakura; Teiichi Yamane; Yukako Ogi; Kaori Ochiai; Daisuke Nakayama (Cardiology and Therapy, 2020)
Abstract Introduction Idarucizumab, a monoclonal antibody fragment, was developed to reverse the anticoagulant effect of dabigatran, and it was approved in Japan in September 2016. An all-case post-marketing surveillance is ongoing to collect data in Japanese patients treated with idarucizumab who had serious bleeding (Group A) or required an urgent procedure (Group B). Methods The primary endpoint was the incidence of adverse drug reactions (ADRs). The secondary endpoint was the maximum extent of reversal of the anticoagulant effect of dabigatran based on activated partial thromboplastin time (aPTT) within 4 h after idarucizumab administration. Results This interim analysis included 262 patients who received idarucizumab. Eighteen patients (6.9%) experienced ADRs within 4 weeks. The reversal effect of idarucizumab based on aPTT within 4 h after idarucizumab administration was assessed in 30 patients and the median maximum percentage reversal was 100%. In Group A, the median time to bleeding cessation in patients without intracranial bleeding was 3.3 h. In Group B, normal intraoperative hemostasis was reported in 63 patients (72.4%). Conclusions The results of this interim analysis suggest that idarucizumab is safe and effective for the reversal of dabigatran in Japanese patients in a real-world setting, and support the continued use of idarucizumab. Trial Registration ClinicalTrials.gov identifier, NCT02946931. Video Abstract